Real Time FPGA Simulation of an Aircraft Engine Model (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, an aero-engine’s thermo-dynamic models are built through complex differential equations that have to be solved iteratively in a stipulated time to predict engine dynamics accurately; an approach to simulate the model using an FPGA with an embedded processor is discussed. Dual core ARM processor ZC702 FPGA is is interfaced with an electronic controller through signal conditioners/ level shifters. The electronic controller feeds the model and the model in turn drives the feedback control system consisting of controller andan actuator.The sensor signals are simulated using Direct Digital Synthesis (DDS) technique. It is found that with 50 MHz clock source, it is possible to generate sinusoidal & TTL waveforms of upto 30 kHz using the on-board clock source.